Factors that affect intention to adopt E-wallet among young adults in Kota Kinabalu, Sabah / Sherllyita Teonny - Teonny, Sherllyita (2020)
Digital wallet which is predicted to be an efficient tool storage and financial management for young adults. Digital wallet to make money we save is well managed is not concerned with the number of shopping scattered returns. But in fact, not all young adults want to switch to the digital technology. This study was made to identify the factors that affect intention to adopt E-wallet among young adults in Kota Kinabalu, Sabah. The technique used in the sampling in this study was the Smart PLS with a sample 99 respondents. Collecting data using the questionnaire method by using Smart Partial Least Square with software SmartPLS 30. The findings revealed that convenience, security and perceived usefulness have positive relationship effect on intention to adopt E-wallet which is indeed a matter of concern for establishing digital wallet among young adults in Kota Kinabalu, Sabah.